Prohibited publications list, 1940 (1940)
1940 1939-1945 "Prohibited publications list, 1940" [HFR0150], 1940 In early 1940, several publishers complained that they had been refused permits to export their publications. At the time of the invasion crisis, there was a tightening of external censorship and on 7 May 1940, the Home Policy Committee instructed the Ministry of Information to prohibit the export of a range of left-wing, communist or fascist papers . This list, issued 28 May 1940, includes the Daily Worker, The New Propellor and Action and came under a category described in the Defence Regulation as 'matter which endangers or brings into disrepute the war effort of this country or its allies'.